AE Test of Calcareous Sands with Particle Rushing - Tan Fengyi; Wang Xinzhi; Hu Mingjian; Wang Ren; Zhu Changqi (Polish Maritime Research, 2017)
The particle of calcareous sands was forced to crush, then the energy from the crushing was released by the form of sound waves. Therefore the AE technique was used to detect the calcareous sands AE signal when it crushed. by to study the AE characteristics, the mechanics of calcareous sands was studied. Study showed that: (1) there was the AE activities on the low confining pressure condition at the beginnig of test, (2) there was more and more AE activities with the continuing of test until to the end, (3) the calcareous sands’ AE activities was on the whole testing, (4) the calcareous sands’ particle crushing and mutual friction played different roles for its AE activities. Then the AE model based on the calcarous sands’ particle crushing was discussed.